Positive electrode active material, positive electrode and lithium secondary battery

JP7638375B2Active Publication Date: 2025-03-03ECOPRO BM CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023533618
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-10-28
Filing Date
2021-11-08
Publication Date
2025-03-03
Estimated Expiration
2041-11-08

AI Technical Summary

Benefits of technology

【0038】 本発明によれば、商用化された他のタイプの正極活物質と比較するとき、電気化学的特性および/または安定性の観点から、様々な不利な部分がある従来のリチウム過剰のリチウムマンガン系酸化物の限界を改善することが可能である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007638375000005
    Figure 0007638375000005
  • Figure 0007638375000006
    Figure 0007638375000006
  • Figure 0007638375000001
    Figure 0007638375000001
Patent Text Reader

Abstract

The present invention relates to a cathode active material and a lithium secondary battery including the same, and more specifically to a cathode active material and a lithium secondary battery including the same, which includes a lithium-excess lithium-manganese-based oxide that is a solid solution of a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group, and in which the lithium-manganese-based oxide has regions in which the proportions of the phase belonging to the C2 / m space group and the phase belonging to the R3-m space group are different, thereby mitigating and / or preventing a decrease in stability caused by the excess lithium and manganese present in the lithium-manganese-based oxide, and a lithium secondary battery including the same.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a positive electrode active material, a positive electrode, and a lithium secondary battery including the same, and more specifically, to a positive electrode active material, a positive electrode, and a lithium secondary battery including the same, which comprises a lithium-excess lithium-manganese-based oxide that is a solid solution of a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group, and in which the lithium-manganese-based oxide has regions in which the ratio of the phase belonging to the C2 / m space group to the phase belonging to the R3-m space group is different, thereby mitigating and / or preventing a decrease in stability caused by the excess lithium and manganese present in the lithium-manganese-based oxide. [Background technology]

[0002] Batteries store electricity by using materials capable of electrochemical reactions at the positive and negative electrodes. A representative example of such batteries is the lithium secondary battery, which stores electrical energy by the difference in chemical potential when lithium ions are intercalated / deintercalated at the positive and negative electrodes.

[0003] The lithium secondary battery is manufactured by using a material capable of reversible intercalation / deintercalation of lithium ions as a positive electrode and a negative electrode active material, and filling an organic electrolyte or a polymer electrolyte between the positive electrode and the negative electrode.

[0004] Lithium composite oxides are used as the positive electrode active material of lithium secondary batteries. Examples of such oxides include LiCoO2, LiMn2O4, LiNiO2, LiMnO2, and composite oxides containing Ni, Co, Mn, Al, etc., as disclosed in Korean Patent Publication No. 10-2015-0069334 (published on June 23, 2015).

[0005] Among the positive electrode active materials, LiCoO2 is the most widely used because of its excellent life characteristics and charge / discharge efficiency. However, it has a drawback in that it is expensive due to the limited availability of cobalt as a raw material, and therefore has limited price competitiveness.

[0006] Lithium manganese oxides such as LiMnO2 and LiMn2O4 have the advantages of being thermally safe and inexpensive, but have problems with small capacity and poor high-temperature characteristics. In addition, LiNiO2-based positive electrode active materials show high discharge capacity battery characteristics, but are difficult to synthesize due to the problem of cation mixing between Li and transition metals, which causes major problems with rate characteristics.

[0007] In addition, a large amount of Li by-products are generated depending on the depth of this cation mixing, and most of these Li by-products consist of compounds of LiOH and Li2CO3, which cause gelation during the manufacture of the positive electrode paste and gas generation during charge and discharge after the electrode is manufactured. The remaining Li2CO3 not only increases the swelling phenomenon of the cell, reducing the cycle, but also causes the battery to swell.

[0008] Various candidate materials for compensating for the shortcomings of conventional positive electrode active materials are being discussed.

[0009] For example, research is being conducted to use lithium-rich lithium manganese oxides, which contain an excess amount of Mn among transition metals and have a lithium content greater than the total content of the transition metals, as a positive electrode active material for lithium secondary batteries. Such lithium-rich lithium manganese oxides are also called overlithiated layered oxides (OLO).

[0010] Although OLO has an advantage of theoretically being able to exhibit high capacity under a high voltage operating environment, it has a disadvantage that the rate capability of a lithium secondary battery using OLO is low because of its relatively low electrical conductivity due to the excessive amount of Mn contained in the oxide. If the rate capability is low, there is a problem in that the charge / discharge capacity and life efficiency (capacity retention) decrease during the charge / discharge cycle of the lithium secondary battery.

[0011] In addition, the decrease in charge / discharge capacity or voltage decay during charge / discharge cycles of a lithium secondary battery using OLO may be induced by a phase transition caused by the movement of transition metals in the lithium manganese oxide. For example, when a phase transition is induced by the movement of transition metals in an unintended direction in a lithium manganese oxide having a layered crystal structure, a spinel or a similar crystal structure may be generated entirely and / or partially in the lithium manganese oxide.

[0012] There have been attempts to solve the above problems with OLO through particle structure and surface modification, such as adjusting the particle size or coating the surface of OLO, but these efforts have not yet reached a commercial level. [Prior art documents] [Patent documents]

[0013] [Patent Document 1] Korean Patent Publication No. 10-2015-0069334 (Published on June 23, 2015) Summary of the Invention [Problem to be solved by the invention]

[0014] In the lithium secondary battery market, the growth of lithium secondary batteries for electric vehicles is playing a leading role, and the demand for positive electrode active materials used in lithium secondary batteries is also continuously changing.

[0015] For example, lithium secondary batteries using LFP have traditionally been used primarily for safety reasons, but recently there has been a trend toward expanding use of nickel-based lithium composite oxides, which have a larger energy capacity per weight than LFP.

[0016] In addition, many nickel-based lithium composite oxides that are currently used as positive electrode active materials for high-capacity lithium secondary batteries essentially use ternary metal elements such as nickel, cobalt, and manganese or nickel, cobalt, and aluminum. Among them, cobalt has problems such as unstable supply and demand and is excessively expensive compared to other raw materials, so there is a need for a new positive electrode active material with a reduced cobalt content or that can eliminate cobalt.

[0017] From this perspective, lithium-rich lithium manganese oxides can meet the aforementioned market expectations, but the electrochemical properties and stability of lithium manganese oxides are still insufficient to replace commercially available NCM or NCA type positive electrode active materials.

[0018] However, when compared with other types of commercially available positive electrode active materials, the conventional lithium-excess lithium manganese-based oxides have disadvantages in terms of electrochemical properties and / or stability. However, the present inventors have confirmed that when the concentration of the transition metal in the lithium manganese-based oxide can be controlled by region, the lithium-excess lithium manganese-based oxide can also exhibit electrochemical properties and stability at a level that allows for commercialization.

[0019] Accordingly, the present invention provides a cathode active material comprising a lithium-excess lithium manganese-based oxide that is a solid solution of a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group, in which the lithium manganese-based oxide has regions in which the ratio of the phase belonging to the C2 / m space group to the phase belonging to the R3-m space group is different, thereby mitigating and / or preventing a decrease in stability caused by the excess lithium and manganese present in the lithium manganese-based oxide.

[0020] Another object of the present invention is to provide a positive electrode active material that includes a lithium-excess lithium manganese-based oxide that is a solid solution of a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group, and that can improve on the low discharge capacity and rate characteristics of conventional lithium-excess lithium manganese-based oxides by controlling the Ni concentration in the region where the phase belonging to the R3-m space group exists to be within a predetermined range.

[0021] Another object of the present invention is to provide a lithium secondary battery in which the low rate characteristics of conventional OLO are improved by using a positive electrode containing the positive electrode active material defined in the present application. [Means for solving the problem]

[0022] According to one aspect of the present invention for solving the above-mentioned technical problems, there is provided a positive electrode active material comprising a lithium-excess lithium-manganese-based oxide containing at least lithium, nickel, and manganese, in which a phase belonging to a C2 / m space group and a phase belonging to an R3-m space group coexist in the lithium-manganese-based oxide, and in which the lithium-manganese-based oxide has regions in which the proportions of the phase belonging to the C2 / m space group and the phase belonging to the R3-m space group differ.

[0023] In an embodiment, the concentration of the metal element in the lithium manganese-based oxide can satisfy the following formula 1:

[0024] [Formula 1] 0.24≦M 2 / M 1 ≦0.55 Where: M 1 is the number of moles of all metal elements (excluding lithium) in the lithium manganese oxide, M 2 is the number of moles of nickel based on all metal elements (excluding lithium) in the lithium manganese oxide.

[0025] In the lithium manganese-based oxide, the content of nickel among the metal elements (excluding lithium) satisfies the formula 1, so that the discharge capacity and rate characteristics, which are reduced due to excess Mn in the lithium manganese-based oxide, can be improved to commercially available levels.

[0026] The lithium manganese oxide may be a core-shell particle including a core and a shell covering at least a part of the surface of the core. In this case, the core and the shell are simply distinguished to refer to regions in the lithium manganese oxide having different ratios of the phase belonging to the C2 / m space group and the phase belonging to the R3-m space group. That is, even if the lithium manganese oxide is a core-shell particle, it should be understood that the core and the shell form a solid solution.

[0027] When the lithium manganese-based oxide is a core-shell particle, a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group may coexist in the core, and the ratio of the phase belonging to the R3-m space group to the phase belonging to the C2 / m space group in the shell may be greater than the ratio of the phase belonging to the R3-m space group to the phase belonging to the C2 / m space group in the core.

[0028] In this case, the concentration of the metal element in the shell can satisfy the following formula 3.

[0029] [Formula 3] 0.24≦M 4 / M 3≦0.75 Where: M 3 is the number of moles of all metal elements (excluding lithium) in the shell, M 4 is the number of moles of nickel based on all metal elements (excluding lithium) in the shell.

[0030] In this case, the ratio of the phase belonging to the R3-m space group to the phase belonging to the C2 / m space group in the lithium manganese-based oxide has an increasing gradient from the core to the shell, thereby reducing abrupt changes in the crystal structure in the lithium manganese-based oxide and preventing damage to particles during charging and discharging.

[0031] The lithium manganese-based oxide may be represented by the following Chemical Formula 1.

[0032] [Chemical formula 1] rLi2MnO3·(1-r)Li a Ni x Co y Mn z M1 1-(x+y+z) O2 Where: M1 is at least one selected from Mo, Nb, Fe, Cr, V, Cu, Zn, Sn, Mg, Ru, Al, Ti, Zr, B, Na, K, Y, P, Ba, Sr, La, Ga, Gd, Sm, W, Ca, Ce, Ta, Sc, In, S, Ge, Si, and Bi; 0 <r≦0.8、0<a≦1、0<x≦1、0≦y<1、0<z<1および0<x+y+z≦1である。

[0033] As shown in Formula 1, the lithium manganese-based oxide defined herein is a solid solution in which a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group coexist within a single particle.

[0034] In this case, a single particle can mean "a non-aggregated particle containing a single primary particle," "a particle formed by aggregating a relatively small number of primary particles," or "a particle formed by aggregating a plurality of (tens to hundreds or more) primary particles."

[0035] In the solid solution represented by the above chemical formula 1, the phase belonging to the C2 / m space group is due to Li2MnO3, and the phase belonging to the R3-m space group is due to Li a Ni x Co y Mn z M1 1-(x+y+z) This is caused by O2.

[0036] According to another aspect of the present invention, there is provided a positive electrode comprising the above-described positive electrode active material.

[0037] According to yet another aspect of the present invention, there is provided a lithium secondary battery using the above-mentioned positive electrode. Effect of the Invention

[0038] According to the present invention, it is possible to improve the limitations of conventional lithium-excess lithium manganese-based oxides, which have various disadvantages in terms of electrochemical properties and / or stability, when compared with other types of commercially available positive electrode active materials.

[0039] First, the lithium manganese-based oxide contained in the positive electrode active material according to the present invention is a lithium-excess lithium manganese-based oxide that is a solid solution of a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group.

[0040] As described above, lithium manganese-based oxides containing excess amounts of lithium and manganese can exhibit high capacity under high voltage operating conditions. However, such lithium manganese-based oxides have the disadvantage of low discharge capacity and rate capability due to the excess lithium and manganese in the oxide. However, when the ratio of the phase belonging to the C2 / m space group and the phase belonging to the R3-m space group is varied by region as in the positive electrode active material according to the present invention, the effect of improving the discharge capacity and rate capability is exhibited.

[0041] In particular, when the ratio of the phase belonging to the R3-m space group to the phase belonging to the C2 / m space group in the surface portion (which can be referred to as the core) of the lithium manganese-based oxide is large, it is possible to alleviate the charge-transfer and / or diffusion of Li ions on the particle surface (which is likely to be mainly caused by the phase belonging to the C2 / m space group), thereby improving the low electrical conductivity of the lithium manganese-based oxide and improving the discharge capacity and rate characteristics, etc., to commercially available levels. [Brief description of the drawings]

[0042] [Figure 1] 1 is a diagram showing the results of TEM analysis of the lithium manganese-based oxide contained in the positive electrode active material according to Example 4. FIG 1 shows a 50 nm-scale TEM image, a 5 nm-scale TEM image obtained by enlarging the area shown in the 50 nm-scale TEM image, and a crystal structure confirmed through FFT transformation of areas A and B of the 5 nm-scale TEM image. [Diagram 2] 2 is a line sum spectrum showing the change in nickel concentration (at%) from the core to the shell of the lithium manganese oxide by line scanning the EDX mapping result of the cross-sectional TEM image of the lithium manganese oxide included in the positive electrode active material according to Example 4. Region A shown in the line sum spectrum of FIG. 2 corresponds to region A of FIG. 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0043] In order to make the present invention easier to understand, certain terms are defined herein for convenience. Unless otherwise defined herein, scientific and technical terms used in the present invention shall have the meanings commonly understood by those of ordinary skill in the art. Furthermore, unless otherwise specified by the context, singular terms shall be understood to include their plural forms, and plural terms shall be understood to include their singular forms.

[0044] Hereinafter, a positive electrode active material including a lithium-rich lithium manganese-based oxide including at least lithium, nickel, manganese, and a doping metal according to the present invention and a lithium secondary battery including the positive electrode active material will be described in more detail.

[0045] positive electrode active material According to one aspect of the present invention, there is provided a positive electrode active material comprising a lithium-rich lithium manganese-based oxide that contains at least lithium, nickel, manganese, and a doping metal, the lithium manganese-based oxide being a composite metal oxide capable of intercalating and deintercalating lithium ions.

[0046] The lithium manganese-based oxide contained in the positive electrode active material defined herein may be a secondary particle including at least one primary particle.

[0047] Here, "secondary particles containing at least one primary particle" should be interpreted as including both "particles formed by agglomeration of multiple primary particles" and "non-agglomerated particles containing a single primary particle."

[0048] The primary particles and the secondary particles may each independently have a rod-like, elliptical and / or irregular shape.

[0049] When the average major axis length is used as an index showing the size of the primary particles and the secondary particles, the average major axis length of the primary particles constituting the lithium manganese oxide may be 0.1 μm to 5 μm, and the average major axis length of the secondary particles may be 1 μm to 30 μm. The average major axis length of the secondary particles may vary depending on the number of the primary particles constituting the secondary particles, and the positive electrode active material may contain particles having various average major axis lengths.

[0050] When the lithium manganese-based oxide is "non-agglomerated particles including a single primary particle" or "particles formed by agglomeration of a relatively small number of primary particles," the size (average particle size) of the primary particles contained in the "non-agglomerated particles including a single primary particle" or "particles formed by agglomeration of a relatively small number of primary particles" may be larger than the size (average particle size) of the primary particles contained in the "secondary particles formed by agglomeration of tens to hundreds or more primary particles."

[0051] Thus, lithium manganese oxides, which are "non-agglomerated particles containing a single primary particle" or "particles formed by agglomeration of a relatively small number of primary particles", generally require stronger heat treatment conditions (high heat treatment temperature / long heat treatment time) than those for producing "secondary particles formed by agglomeration of tens to hundreds or more primary particles". For example, it is known that when heat treatment is performed for a long time at a relatively high temperature (800°C or higher), particle growth (crystal growth) is promoted to increase the size of a single particle, and at the same time, a positive electrode active material with a low degree of particle agglomeration is obtained.

[0052] For example, when the lithium manganese oxide is "non-agglomerated particles including a single primary particle" or "particles formed by agglomeration of a relatively small number of primary particles," the primary particles may have an average major axis length in the range of 0.5 μm to 20 μm. On the other hand, when the lithium manganese oxide is "particles formed by agglomeration of a plurality of (tens to hundreds or more) primary particles," the primary particles may have an average major axis length in the range of 0.1 μm to 5 μm.

[0053] The primary particles may also include at least one crystallite, i.e., the primary particles may consist of a single crystallite or may exist as particles containing multiple crystallites.

[0054] The lithium manganese-based oxide defined in the present application is a composite metal oxide containing an excess amount of lithium and manganese, in which a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group coexist, i.e., the lithium manganese-based oxide is a solid solution of a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group.

[0055] In the present application, the term "solid solution" means that a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group exist as a single particle in the lithium manganese-based oxide.

[0056] In this case, a single particle can mean "a non-aggregated particle containing a single primary particle," "a particle formed by aggregating a relatively small number of primary particles," or "a particle formed by aggregating a plurality of (tens to hundreds or more) primary particles."

[0057] In this application, the term "solid solution" does not mean a state in which a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group present in the lithium manganese-based oxide are physically and / or chemically bonded or attached to each other.

[0058] For example, a metal oxide having a phase belonging to the R3-m space group, which is obtained by mixing a metal oxide having a phase belonging to the C2 / m space group with a metal oxide having a phase belonging to the R3-m space group, and which has a surface-coated metal oxide having a phase belonging to the C2 / m space group, does not qualify as a solid solution.

[0059] In addition, the lithium manganese-based oxide may have regions in which a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group coexist, and in which the ratio of the phase belonging to the C2 / m space group to the phase belonging to the R3-m space group is different.

[0060] In this way, when the ratio of the phase belonging to the C2 / m space group and the phase belonging to the R3-m space group in the lithium manganese-based oxide is varied depending on the region, the discharge capacity and rate characteristics of the positive electrode active material containing the lithium manganese-based oxide can be improved.

[0061] Moreover, the concentration of the metal element in the lithium manganese-based oxide can satisfy the following formula 1.

[0062] [Formula 1] 0.24≦M 2 / M 1 ≦0.55 Where: M 1 is the number of moles of all metal elements (excluding lithium) in the lithium manganese oxide, M 2 is the number of moles of nickel based on all metal elements (excluding lithium) in the lithium manganese oxide.

[0063] In the above formula 1, M 2 / M 1 If the ratio exceeds 0.55, the content of Ni in the lithium manganese-based oxide becomes excessively high, and cation mixing with Li may occur, so that the lithium manganese-based oxide is unlikely to exhibit the characteristics of an OLO.

[0064] As described above, since the lithium manganese-based oxide according to the present invention contains excess lithium, when the content of Ni in the lithium manganese-based oxide is high, cation mixing becomes intense and the amount of lithium impurities such as LiOH and Li2CO3 in the lithium manganese-based oxide can increase. The lithium impurities are the main cause of gelation of the paste when a positive electrode paste is prepared using the positive electrode active material, and swelling of the cell during charge and discharge after the preparation of the positive electrode.

[0065] On the other hand, in the formula 1, M 2 / M 1 If the ratio is less than 0.24, the Ni content in the lithium manganese oxide is insufficient, making it difficult to improve the charge-transfer and / or diffusion of Li ions, which are reduced by an excess of manganese.

[0066] That is, by making the nickel content in the lithium manganese-based oxide satisfy the formula 1, it is possible to improve the discharge capacity and rate characteristics, which are reduced due to the excess Mn in the lithium manganese-based oxide, to commercially available levels.

[0067] In addition, in the lithium manganese-based oxide, nickel exists in a phase belonging to the R3-m space group, but does not exist in a phase belonging to the C2 / m space group, so the nickel content in the lithium manganese-based oxide can be expressed by the following formula 2.

[0068] [Formula 2] 0.40≦M 2′ / M 1′ ≦0.70 Here, M 1′ is the number of moles of all metallic elements (excluding lithium) in the phase belonging to the R3-m space group, M 2′ is the number of moles of nickel based on all metal elements (excluding lithium) in the phase belonging to the R3-m space group.

[0069] In the above formula 2, M 2′ / M 1′ When M exceeds 0.70, the content of Ni in the phase belonging to the R3-m space group becomes excessively high, and cation mixing with Li may occur. 2′ / M 1′ When is less than 0.40, the Ni content in the phase belonging to the R3-m space group becomes insufficient, and manganese is present in excess, which may decrease the charge-transfer and / or diffusion of Li ions.

[0070] The lithium manganese-based oxide may be a core-shell particle comprising a core and a shell covering at least a portion of the surface of the core.

[0071] In this case, the core and the shell are simply distinguished to refer to regions in the lithium manganese-based oxide in which the ratio of the phase belonging to the C2 / m space group to the phase belonging to the R3-m space group is different. That is, even if the lithium manganese-based oxide is a core-shell particle, it should be understood that the core and the shell form a solid solution.

[0072] In this case, the shell (or surface portion) and core (or center portion) of the particle can be distinguished by the concentration of any metal element present in that region, or by the proportion of phases (crystal structures) present in that region, as described below.

[0073] The shell may occupy at least a part of the surface of the core. That is, the shell may be present partially on the surface of the core, or may occupy the entire surface of the core. When the radius of the core-shell particle is r, the thickness of the shell may be 0.001r to 0.9r, but is not necessarily limited thereto. As described above, the core and the shell are distinguished by the concentration of an arbitrary metal element, or by the ratio of a phase (crystal structure) present in the region, as described below.

[0074] In one embodiment, the lithium manganese-based oxide may have a region in which a phase belonging to the R3-m space group is predominantly present, i.e., when the ratio of the phase belonging to the R3-m space group in a region in which a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group coexist in the lithium manganese-based oxide is greater than the ratio of the phase belonging to the C2 / m space group in the lithium manganese-based oxide, the region can be defined as a region in which the phase belonging to the R3-m space group is predominantly present.

[0075] For example, when the lithium manganese oxide is a core-shell particle, the phase belonging to the C2 / m space group and the phase belonging to the R3-m space group may coexist in the core and the shell, and the ratio of the phase belonging to the R3-m space group to the phase belonging to the C2 / m space group in the core and the ratio of the phase belonging to the R3-m space group to the phase belonging to the C2 / m space group in the shell may be different. In this case, the phase belonging to the R3-m space group may be predominant in one of the regions of the core and the shell.

[0076] In addition, when the phase belonging to the C2 / m space group and the phase belonging to the R3-m space group coexist in the core and shell of the lithium manganese-based oxide, the ratio of the phase belonging to the R3-m space group to the phase belonging to the C2 / m space group in the shell is preferably greater than the ratio of the phase belonging to the R3-m space group to the phase belonging to the C2 / m space group in the core. The ratio of the phase belonging to the R3-m space group to the phase belonging to the C2 / m space group in the core and the shell can be confirmed through the Ni content in the core and the shell.

[0077] In another embodiment, when the lithium manganese-based oxide is a core-shell particle, the core may contain a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group, and the shell may contain only a phase belonging to the R3-m space group.

[0078] In the core-shell particles according to various embodiments described above, the concentration of the metal element in the shell can satisfy the following formula 3:

[0079] [Formula 3] 0.24≦M 4 / M 3 ≦0.75 Where: M 3 is the number of moles of all metal elements (excluding lithium) in the shell, M 4 is the number of moles of nickel based on all metal elements (excluding lithium) in the shell.

[0080] In addition, in the lithium manganese-based oxide, nickel exists in a phase belonging to the R3-m space group, but does not exist in a phase belonging to the C2 / m space group, so the content of nickel in the shell can be expressed by the following formula 4.

[0081] [Formula 4] 0.40≦M 4′ / M 3′ ≦0.75 Here, M 3′ is the number of moles of all metallic elements (excluding lithium) in the phases belonging to the R3-m space group in said shell, M 4′ is the number of moles of nickel based on all metal elements (excluding lithium) in the phases belonging to the R3-m space group in said shell.

[0082] In the formula 3 or 4, M 4 / M 3 or M 4′ / M 3′ When M exceeds 0.75, the content of Ni in the phase belonging to the R3-m space group becomes excessively high, and cation mixing with Li may occur. 4 / M 3 is smaller than 0.24, or M 4′ / M 3′When is smaller than 0.40, the Ni content in the phase belonging to the R3-m space group becomes insufficient and manganese is present in excess, which may decrease the charge-transfer and / or diffusion of Li ions.

[0083] In the case of the core-shell particles according to the various embodiments described above, a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group coexist in the lithium manganese-based oxide core, so that the instability of the phase belonging to the C2 / m space group can be partially offset by the phase belonging to the R3-m space group.

[0084] In addition, since the shell of the lithium manganese oxide is dominated by a phase belonging to the R3-m space group, it is possible to alleviate charge-transfer and / or diffusion of Li ions on the particle surface, which is likely to be caused mainly by a phase belonging to the C2 / m space group, unlike conventional lithium manganese oxides.

[0085] It is also well known that lithium-excess lithium manganese oxides containing excessive Mn have lower electrical conductivity than LCO or NCM or NCA containing excessive Ni. In addition, there is a problem in that the electrical conductivity decreases as the Mn content increases in general NCM.

[0086] Various reactions can occur on the surface of the positive electrode active material. As the Mn content in the positive electrode active material increases, the charge-transfer and / or diffusion of Li ions on the surface is hindered, and this phenomenon can be called the surface kinetic or surface reaction kinetic decrease.

[0087] In addition, the ratio of the phase belonging to the R3-m space group to the phase belonging to the C2 / m space group in the lithium manganese-based oxide may have an increasing gradient from the core to the shell.

[0088] A gradient is formed in which the ratio of the phase belonging to the R3-m space group to the phase belonging to the C2 / m space group increases from the core to the shell, thereby reducing abrupt changes in crystal structure between the core and the shell, and allowing the phase belonging to the C2 / m space group and the phase belonging to the R3-m space group to stably form a solid solution in the lithium manganese-based oxide.

[0089] If there is a sudden change between a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group in the lithium manganese oxide, a transition metal may move in an unintended direction in the lithium manganese oxide during charge-discharge cycles, causing a phase transition (change in crystal structure).

[0090] As described above, the surface kinetics of the lithium manganese-based oxide can be improved by having the concentrations of metal elements in the region in the core where the phase belonging to the R3-m space group exists and in the shell satisfy the above-mentioned formulas 1 to 4.

[0091] The lithium manganese-based oxide defined herein may be represented by the following Chemical Formula 1:

[0092] [Chemical formula 1] rLi2MnO3·(1-r)Li a Ni x Co y Mn z M1 1-(x+y+z )O2 Where: M1 is at least one selected from Mo, Nb, Fe, Cr, V, Cu, Zn, Sn, Mg, Ru, Al, Ti, Zr, B, Na, K, Y, P, Ba, Sr, La, Ga, Gd, Sm, W, Ca, Ce, Ta, Sc, In, S, Ge, Si, and Bi; 0 <r≦0.8、0<a≦1、0<x≦1、0≦y<1、0<z<1および0<x+y+z≦1である。

[0093] The lithium manganese-based oxide represented by Chemical Formula 1 may selectively contain cobalt. In addition, when the lithium manganese-based oxide contains cobalt, the ratio of the number of moles of the cobalt to the number of moles of all metal elements in the lithium manganese-based oxide may be 10% or less.

[0094] The lithium manganese oxide represented by the chemical formula 1 is a mixture of a C2 / m phase oxide represented by Li2MnO3 and Li a Ni x Co y Mn z M1 1-(x+y+z) It is a complex oxide in which the R3-m phase oxide, represented by O2, coexists. In this case, the C2 / m phase oxide and the R3-m phase oxide exist in a solid solution state.

[0095] In addition, in the lithium manganese-based oxide represented by Chemical Formula 1, when r exceeds 0.8, the ratio of Li2MnO3, which is an oxide of the C2 / m phase, in the lithium manganese-based oxide becomes excessively high, and the discharge capacity of the positive electrode active material may decrease.

[0096] Lithium secondary battery According to another aspect of the present invention, there is provided a positive electrode including a positive electrode current collector and a positive electrode active material layer formed on the positive electrode current collector, wherein the positive electrode active material layer may include the lithium manganese-based oxide according to any of the various embodiments of the present invention as a positive electrode active material.

[0097] Therefore, a detailed description of the lithium manganese-based oxide will be omitted, and only the remaining components not described above will be described below. For convenience, the lithium manganese-based oxide will be referred to as the positive electrode active material below.

[0098] The positive electrode current collector is not particularly limited as long as it does not induce chemical changes in the battery and has conductivity, and may be, for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. The positive electrode current collector may usually have a thickness of 3 to 500 μm, and fine irregularities may be formed on the surface of the current collector to increase the adhesive strength of the positive electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0099] The positive electrode active material layer may be prepared by coating a positive electrode slurry composition containing the positive electrode active material, a conductive material, and optionally a binder, on the positive electrode current collector.

[0100] At this time, the positive electrode active material may be included in an amount of 80 to 99 wt%, more specifically, 85 to 98.5 wt%, based on the total weight of the positive electrode active material layer. When included in this content range, excellent capacity characteristics can be exhibited, but the amount is not necessarily limited thereto.

[0101] The conductive material is used to impart electrical conductivity to the electrode, and can be used without any particular limitation as long as it has electronic conductivity without causing chemical changes in the battery that is constructed. Specific examples include graphite such as natural graphite and artificial graphite, carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, carbon-based materials such as carbon fibers, metal powders or metal fibers such as copper, nickel, aluminum, and silver, conductive whiskers such as zinc oxide and potassium titanate, conductive metal oxides such as titanium oxide, and conductive polymers such as polyphenylene derivatives, and the like, and one or more of these may be used alone or in combination. The conductive material may be contained in an amount of 0.1 to 15% by weight based on the total weight of the positive electrode active material layer.

[0102] The binder plays a role of improving the adhesion between the positive electrode active material particles and the adhesive strength between the positive electrode active material and the current collector. Specific examples include polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinyl alcohol, polyacrylonitrile, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated-EPDM, styrene-butadiene rubber (SBR), fluororubber, or various copolymers thereof, and among these, one type alone or a mixture of two or more types may be used. The binder may be contained in an amount of 0.1 to 15% by weight based on the total weight of the positive electrode active material layer.

[0103] The positive electrode may be manufactured by a typical method for manufacturing a positive electrode, except for using the positive electrode active material. Specifically, the positive electrode may be manufactured by dissolving or dispersing the positive electrode active material and, optionally, a binder and a conductive material in a solvent to prepare a positive electrode slurry composition, which is then coated on a positive electrode current collector, followed by drying and rolling.

[0104] The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, or water, and one or more of these may be used alone or in combination. The amount of the solvent used is sufficient to dissolve or disperse the positive electrode active material, conductive material, and binder, and to provide a viscosity that allows excellent thickness uniformity when applied to manufacture a positive electrode, taking into consideration the coating thickness of the slurry and the production yield.

[0105] In another embodiment, the positive electrode may be manufactured by casting the positive electrode slurry composition on a separate support, peeling the positive electrode slurry composition from the support, and laminating the resulting film on a positive electrode current collector.

[0106] According to yet another aspect of the present invention, there may be provided an electrochemical device including the above-mentioned positive electrode. The electrochemical device may be, for example, a battery or a capacitor, and more specifically, a lithium secondary battery.

[0107] Specifically, the lithium secondary battery may include a positive electrode, a negative electrode facing the positive electrode, and a separator and an electrolyte interposed between the positive electrode and the negative electrode. Here, since the positive electrode is as described above, a detailed description thereof will be omitted for convenience, and only the remaining components not described above will be described in detail below.

[0108] The lithium secondary battery may optionally further include a battery container that houses an electrode assembly of the positive electrode, the negative electrode, and the separator, and a sealing member that seals the battery container.

[0109] The negative electrode may include a negative electrode current collector and a negative electrode active material layer located on the negative electrode current collector.

[0110] The negative electrode current collector is not particularly limited as long as it has high conductivity without inducing chemical changes in the battery, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may generally have a thickness of 3 μm to 500 μm, and like the positive electrode current collector, the surface of the current collector may be formed with fine irregularities to strengthen the binding force of the negative electrode active material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, or nonwoven fabric.

[0111] The negative electrode active material layer may be prepared by coating a negative electrode slurry composition containing the negative electrode active material, a conductive material, and optionally a binder, on the negative electrode current collector.

[0112] The negative electrode active material may be a compound capable of reversible intercalation and deintercalation of lithium. Specific examples of the negative electrode active material include carbonaceous materials such as artificial graphite, natural graphite, graphitized carbon fiber, and amorphous carbon, metallic compounds capable of alloying with lithium such as Si, Al, Sn, Pb, Zn, Bi, In, Mg, Ga, Cd, Si alloys, Sn alloys, and Al alloys, and SiO β (0<β<2), metal oxides capable of doping and dedoping lithium, such as SnO2, vanadium oxide, and lithium vanadium oxide, or composites containing the metallic compounds and carbonaceous materials, such as Si-C composites and Sn-C composites, may be used. A metallic lithium thin film may be used as the negative electrode active material. Low-crystalline carbon and high-crystalline carbon may both be used as the carbon material. Representative examples of low crystalline carbon include soft carbon and hard carbon, and representative examples of high crystalline carbon include amorphous, plate-like, flake-like, spherical or fibrous natural graphite or artificial graphite, kish graphite, pyrolytic carbon, mesophase pitch based carbon fiber, carbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes.

[0113] The negative electrode active material may be included in an amount of 80 to 99 wt % based on the total weight of the negative electrode active material layer.

[0114] The binder is a component that aids in bonding between the conductive material, the active material, and the current collector, and may be added in an amount of usually 0.1 to 10 wt% based on the total weight of the negative electrode active material layer. Examples of such binders include polyvinylidene fluoride (PVDF), polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, tetrafluoroethylene, polyethylene, polypropylene, ethylene-propylene-diene polymer (EPDM), sulfonated EPDM, styrene-butadiene rubber, nitrile-butadiene rubber, fluororubber, and various copolymers thereof.

[0115] The conductive material may be added as a component for further improving the conductivity of the negative electrode active material in an amount of 10% by weight or less, preferably 5% by weight or less, based on the total weight of the negative electrode active material layer. Such a conductive material is not particularly limited as long as it has conductivity without inducing a chemical change in the battery, and may be, for example, graphite such as natural graphite or artificial graphite, carbon black such as acetylene black, ketjen black, channel black, furnace black, lamp black, or thermal black, conductive fibers such as carbon fibers or metal fibers, metal powders such as carbon fluoride, aluminum, or nickel powder, conductive whiskers such as zinc oxide or potassium titanate, conductive metal oxides such as titanium oxide, or conductive materials such as polyphenylene derivatives.

[0116] In one embodiment, the negative electrode active material layer may be prepared by coating a negative electrode slurry composition prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent on a negative electrode current collector and drying the coating. Alternatively, the negative electrode slurry composition may be cast on a separate support, and then peeled off from the support to obtain a film, which may be laminated on the negative electrode current collector.

[0117] In another embodiment, the negative electrode active material layer may be manufactured by coating a negative electrode slurry composition prepared by dissolving or dispersing a negative electrode active material, and optionally a binder and a conductive material, in a solvent on a negative electrode current collector and drying the coating, or by casting the negative electrode slurry composition on a separate support and peeling the composition from the support to obtain a film, which may be laminated on the negative electrode current collector.

[0118] Meanwhile, in the lithium secondary battery, the separator separates the negative electrode and the positive electrode to provide a path for lithium ions to move. Any separator that is generally used as a separator in a lithium secondary battery may be used without any particular limitation. In particular, it is preferable that the separator has low resistance to ion movement of the electrolyte and has excellent electrolyte humidification ability. Specifically, a porous polymer film, for example, a porous polymer film made of a polyolefin-based polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, and an ethylene / methacrylate copolymer, or a laminate structure of two or more layers thereof may be used. In addition, a conventional porous nonwoven fabric, for example, a nonwoven fabric made of high-melting point glass fiber, polyethylene terephthalate fiber, etc. may be used. In addition, in order to ensure heat resistance or mechanical strength, a coated separator containing a ceramic component or a polymer material may be used, and may be selectively used as a single layer or multilayer structure.

[0119] In addition, examples of the electrolyte used in the present invention include organic liquid electrolytes, inorganic liquid electrolytes, solid polymer electrolytes, gel polymer electrolytes, solid inorganic electrolytes, and molten inorganic electrolytes that can be used in the production of lithium secondary batteries, but are not limited to these.

[0120] Specifically, the electrolyte may include an organic solvent and a lithium salt.

[0121] The organic solvent may be used without any particular limitation as long as it serves as a medium through which ions involved in the electrochemical reaction of the battery can move. Specifically, the organic solvent may be an ester solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, or ε-caprolactone, an ether solvent such as dibutyl ether or tetrahydrofuran, a ketone solvent such as cyclohexanone, an aromatic hydrocarbon solvent such as benzene or fluorobenzene, dimethylcarbonate (DMC), diethylcarbonate (DEC), methylethylcarbonate (MEC), ethylmethylcarbonate (EMC), ethylene carbonate (EC), or propylene carbonate (propylene carbonate). Examples of the solvents that may be used include carbonate-based solvents such as ethylene carbonate (PC), alcohol-based solvents such as ethyl alcohol and isopropyl alcohol, nitriles such as R-CN (R is a straight-chain, branched or cyclic hydrocarbon group having 2 to 20 carbon atoms, which may contain a double bond aromatic ring or an ether bond), amides such as dimethylformamide, dioxolanes such as 1,3-dioxolane, and sulfolanes. Among these, carbonate-based solvents are preferred, and a mixture of a cyclic carbonate (e.g., ethylene carbonate or propylene carbonate) having high ionic conductivity and high dielectric constant that can improve the charge / discharge performance of a battery and a low-viscosity linear carbonate compound (e.g., ethyl methyl carbonate, dimethyl carbonate or diethyl carbonate) is more preferred. In this case, the performance of the electrolyte may be excellent if the cyclic carbonate and the chain carbonate are mixed at a volume ratio of about 1:1 to about 1:9.

[0122] The lithium salt may be used without any particular limitation as long as it is a compound capable of providing lithium ions used in a lithium secondary battery. Specifically, the lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3), LiN(C2F5SO2)2, LiN(CF3SO2)2, LiCl, LiI, or LiB(C2O4)2. The concentration of the lithium salt is preferably used within a range of 0.1 to 2.0M. When the concentration of the lithium salt is within the above range, the electrolyte has appropriate conductivity and viscosity, so that excellent electrolyte performance can be exhibited and lithium ions can be effectively transferred.

[0123] In addition to the electrolyte components, the electrolyte may further contain one or more additives such as haloalkylene carbonate compounds such as difluoroethylene carbonate, pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinoneimine dyes, N-substituted oxazolidinones, N,N-substituted imidazolidines, ethylene glycol dialkyl ethers, ammonium salts, pyrrole, 2-methoxyethanol, or aluminum trichloride, for the purpose of improving the life characteristics of the battery, suppressing the decrease in battery capacity, improving the discharge capacity of the battery, etc. In this case, the additives may be contained in an amount of 0.1 to 5% by weight based on the total weight of the electrolyte.

[0124] As described above, the lithium secondary battery including the positive electrode active material according to the present invention stably exhibits excellent discharge capacity, output characteristics and life characteristics, and is therefore useful in the fields of portable devices such as mobile phones, notebook computers, and digital cameras, and electric vehicles such as hybrid electric vehicles (HEVs).

[0125] The external shape of the lithium secondary battery according to the present invention is not particularly limited, and may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, etc. Furthermore, the lithium secondary battery can be used not only as a battery cell used as a power source for a small device, but also preferably as a unit battery for a medium- to large-sized battery module including a plurality of battery cells.

[0126] According to yet another aspect of the present invention, there may be provided a battery module including the lithium secondary battery as a unit cell and / or a battery pack including the same.

[0127] The battery module or the battery pack can be used as a power source for one or more medium- to large-sized devices, such as a power tool, an electric vehicle (Electric Vehicle (EV), a hybrid electric vehicle, and a plug-in hybrid electric vehicle (PHEV), or a power storage system.

[0128] The present invention will be described in more detail below with reference to examples. However, these examples are for the purpose of illustrating the present invention, and the scope of the present invention is not to be construed as being limited by these examples.

[0129] Production Example 1. Production of positive electrode active material Example 1. (a) Preparation of precursor The reactor was stirred while being charged with a mixed aqueous solution of NiSO4·6H2O and MnSO4·H2O in a molar ratio of 25:75, NaOH and NH4OH. The temperature inside the reactor was kept at 45°C, and the precursor synthesis reaction was carried out while N2 gas was fed into the reactor. After the reaction was completed, the reactor was washed and dehydrated, and the Ni 0.25 Mn 0.75 The (OH)2 precursor was obtained.

[0130] (b) First heat treatment The temperature of a firing furnace in an O2 atmosphere was increased at a rate of 2°C / min, and then the temperature was kept at 550°C, and the precursor obtained in step (a) was heat-treated for 5 hours, followed by furnace cooling.

[0131] (c) Second heat treatment The oxide precursor obtained in step (b) was mixed with LiOH (Li / (metal other than Li) molar ratio=1.55) as a lithium compound to prepare a mixture. Next, the temperature of a sintering furnace in an O2 atmosphere was increased at a rate of 2°C / min, and the mixture was heat-treated for 8 hours at 900°C. The mixture was then cooled in the furnace to obtain a positive electrode active material containing a lithium-excess lithium-manganese oxide. As a result of ICP analysis, the positive electrode active material according to Example 1 was 0.54Li2MnO3·0.46LiNi 0.538 Mn 0.462 It was confirmed that it had an O2 composition.

[0132] Example 2 Ni 0.40 Mn 0.60 A positive electrode active material was prepared in the same manner as in Example 1, except that the (OH)2 precursor was used and LiOH was mixed at a molar ratio of 1.25 (Li / (metal other than Li) molar ratio=1.25) before the second heat treatment. As a result of ICP analysis, the positive electrode active material of Example 2 was 0.23Li2MnO3·0.77LiNi 0.523 Mn 0.477 It was confirmed that it had an O2 composition.

[0133] Example 3 Ni 0.45 Mn 0.55 A positive electrode active material was prepared in the same manner as in Example 1, except that the (OH)2 precursor was used and LiOH was mixed at a molar ratio of 1.20 (Li / (metal other than Li) molar ratio=1.20) before the second heat treatment. As a result of ICP analysis, the positive electrode active material of Example 3 was 0.19Li2MnO3·0.81LiNi 0.557 Mn0.443 It was confirmed that it had an O2 composition.

[0134] Example 4 (a) Preparation of precursor The reactor was charged with a mixture of NiSO4·6H2O and MnSO4·H2O in a molar ratio of 40:60, NaOH, and NH4OH while stirring. The temperature inside the reactor was kept at 45°C, and the precursor synthesis reaction was carried out while feeding N2 gas into the reactor. After the reaction was completed, the reactor was washed and dehydrated, and the Ni 0.40 Mn 0.60 The (OH)2 precursor was obtained.

[0135] (b) Precursor coating CoSO4·7H2O aqueous solution, NaOH, and NH4OH were added to the reactor in which the precursor obtained in step (a) was stirred. At this time, CoSO4·7H2O was weighed out so that it was 10 mol% and then added. After the reaction was completed, the mixture was washed and dehydrated, and then dried at 150℃ for 14 hours to obtain a coated precursor.

[0136] (c) First heat treatment The temperature of a firing furnace in an O2 atmosphere was increased at a rate of 2°C / min, and then the temperature was kept at 550°C, and the precursor obtained in step (b) was heat-treated for 5 hours, followed by furnace cooling.

[0137] (d) Second heat treatment The oxide precursor obtained in step (c) was mixed with LiOH (Li / (metal other than Li) molar ratio=1.25) as a lithium compound to prepare a mixture. Next, the temperature of a sintering furnace in an O2 atmosphere was increased at a rate of 2°C / min, and the mixture was heat-treated for 8 hours at 850°C. The mixture was then cooled in the furnace to obtain a positive electrode active material containing a lithium-excess lithium-manganese oxide. As a result of ICP analysis, the positive electrode active material of Example 3 was 0.23Li2MnO3·0.77LiNi 0.46 7Co 0.127 Mn 0.405It was confirmed that it had an O2 composition.

[0138] Comparative Example 1 A positive electrode active material was prepared in the same manner as in Example 1, except that LiOH was mixed at a molar ratio of 1.35 (Li / (metal other than Li) molar ratio=1.35) before the second heat treatment. As a result of ICP analysis, the positive electrode active material of Comparative Example 1 was 0.36Li2MnO3·0.64LiNi 0.389 Mn 0.611 It was confirmed that it had an O2 composition.

[0139] Comparative Example 2 A positive electrode active material was produced in the same manner as in Example 2, except that LiOH was mixed at a molar ratio of 1.50 (Li / (metal other than Li) molar ratio=1.50) before the second heat treatment. As a result of ICP analysis, the positive electrode active material of Comparative Example 2 was 0.49Li2MnO3·0.51LiNi 0.793 Mn 0.207 It was confirmed that it had an O2 composition.

[0140] Manufacturing Example 2. Manufacturing of lithium secondary batteries A positive electrode slurry was prepared by dispersing 90 wt% of the positive electrode active material prepared in Preparation Example 1, 5.5 wt% of carbon black, and 4.5 wt% of PVDF binder in 30 g of N-methyl-2-pyrrolidone (NMP). The positive electrode slurry was uniformly applied to a thin aluminum film having a thickness of 15 μm and dried in a vacuum at 135° C. to prepare a positive electrode for a lithium secondary battery.

[0141] A coin battery was fabricated using a lithium foil as a counter electrode for the positive electrode, a porous polyethylene film (Celgard 2300, thickness: 25 μm) as a separator, and an electrolyte solution of LiPF6 at a concentration of 1.15 M in a solvent of ethylene carbonate and ethyl methyl carbonate mixed in a volume ratio of 3:7.

[0142] Experimental Example 1. TEM analysis of lithium manganese oxide The lithium manganese oxides contained in each of the positive electrode active materials prepared in Preparation Example 1 were selected, and then cross-sectioned using a cross-section Polisher (accelerating voltage 5.0 kV, milling for 4 hours), followed by obtaining cross-sectional TEM images using a transmission electron microscope. Next, the TEM images were subjected to FFT (Fast Fourier Transform) to create diffraction patterns, which were then indexed to confirm the crystal structures in the core and shell regions of the lithium manganese oxides.

[0143] 1 is a diagram showing the results of TEM analysis of the lithium manganese-based oxide contained in the positive electrode active material according to Example 4. FIG 1 shows a 50 nm-scale TEM image, a 5 nm-scale TEM image obtained by enlarging the area shown in the 50 nm-scale TEM image, and a crystal structure confirmed through FFT transformation of areas A and B of the 5 nm-scale TEM image.

[0144] In this case, the crystal structure in the shell region was confirmed in a region at a distance of 0 to 0.03 μm from the outermost periphery of the lithium manganese-based oxide, and the crystal structure in the core region was confirmed in a region at a distance of 0.12 to 0.15 μm from the outermost periphery of the lithium manganese-based oxide.

[0145] The analysis results are shown in Table 1 below.

[0146] [Table 1]

[0147] In addition, EDX mapping was performed on the cross-sectional TEM images of the lithium manganese-based oxides contained in each of the positive electrode active materials prepared by Preparation Example 1, and the EDX mapping results were subjected to line scanning to confirm the change in nickel concentration (at%) from the shell to the core of the lithium manganese-based oxide.

[0148] In this case, the nickel concentration in the shell region was expressed as the average nickel concentration (at%) based on the lithium manganese-based oxide (bulk) measured from a region at a distance of 0 to 0.03 μm from the outermost periphery of the lithium manganese-based oxide, and the average nickel concentration (at%) converted based on the R3-m phase in the lithium manganese-based oxide.

[0149] In addition, the nickel concentration in the core region is expressed as the average nickel concentration (at%) based on the lithium manganese-based oxide (bulk) measured in a region 0.12 to 0.15 μm away from the outermost periphery of the lithium manganese-based oxide, and the average nickel concentration (at%) converted based on the R3-m phase in the lithium manganese-based oxide.

[0150] In addition, the nickel concentration in the intermediate region is expressed as the average nickel concentration (at%) based on the lithium manganese-based oxide (bulk) measured in a region at a distance of 0.075 to 0.1 μm from the outermost periphery of the lithium manganese-based oxide, and the average nickel concentration (at%) converted based on the R3-m phase in the lithium manganese-based oxide.

[0151] 2 is a line sum spectrum showing the change in nickel concentration (at%) from the core to the shell of the lithium manganese oxide by line scanning the EDX mapping result of the cross-sectional TEM image of the lithium manganese oxide included in the positive electrode active material according to Example 4. Region A shown in the line sum spectrum of FIG. 2 corresponds to region A of FIG. 1.

[0152] The analysis results are shown in Table 2 below.

[0153] [Table 2]

[0154] Referring to the results in Table 1, it can be seen that the lithium manganese-based oxides contained in each of the positive electrode active materials prepared according to Preparation Example 1 have a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group coexisting in a single particle. In other words, the lithium manganese-based oxides contained in each of the positive electrode active materials prepared according to Preparation Example 1 are solid solutions represented by the following Chemical Formula 1:

[0155] [Chemical formula 1] rLi2MnO3·(1-r)Li a Ni x Co y Mn z M1 1-(x+y+z) O2

[0156] The phase belonging to the C2 / m space group in the solid solution is due to Li2MnO3, and the phase belonging to the R3-m space group is due to Li a Ni x Co y Mn z M1 1-(x+y+z) It is expected that this is due to O2. In addition, it can be confirmed that the lithium manganese oxides contained in the positive electrode active materials according to Examples 1 to 3 have regions in which the ratio of the phase belonging to the C2 / m space group to the phase belonging to the R3-m space group is different.

[0157] In addition, referring to the results of Tables 1 and 2, it can be confirmed that a phase belonging to the R3-m space group and a phase belonging to the C2 / m space group coexist in the core region and shell region of the lithium manganese-based oxide contained in the positive electrode active materials of Examples 1 to 3, and that the lithium manganese-based oxide has a plurality of regions having different ratios of the phase belonging to the C2 / m space group and the phase belonging to the R3-m space group.

[0158] In addition, referring to the results of Table 2 and FIG. 2, it can be seen that a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group coexist in the core region of the lithium manganese-based oxide contained in the cathode active material of Example 4, whereas only a phase belonging to the R3-m space group exists in the shell region, and the nickel concentration in the lithium manganese-based oxide has a gradient that increases from the core to the shell.

[0159] Considering that the phase belonging to the R3-m space group and the phase belonging to the C2 / m space group constituting the lithium manganese-based oxide in which nickel exists is a phase belonging to the R3-m space group, the above result means that the ratio of the phase belonging to the R3-m space group increases from the core to the shell of the lithium manganese-based oxide, and thus the ratio of the phase belonging to the R3-m space group to the phase belonging to the C2 / m space group in the lithium manganese-based oxide has a gradient that increases from the core to the shell.

[0160] Meanwhile, it can be seen that in both the core and shell of the lithium manganese-based oxide contained in the positive electrode active materials according to Comparative Example 1 and Comparative Example 2, a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group coexist, and there is no significant difference between the average nickel concentration in the shell and the average nickel concentration in the core.

[0161] That is, it can be confirmed that there are no regions with different ratios of the phase belonging to the C2 / m space group and the phase belonging to the R3-m space group in the lithium manganese-based oxide contained in the positive electrode active materials according to Comparative Example 1 and Comparative Example 2. The above results indicate that the lithium manganese-based oxide contains a phase belonging to the C2 / m space group and a phase belonging to the R3-m space group in a uniform solid solution state.

[0162] Experimental Example 2: Evaluation of the electrochemical properties of lithium secondary batteries The lithium secondary battery (coin cell) manufactured in Manufacturing Example 2 was subjected to a charge-discharge experiment at 25° C., voltage range of 2.0 V to 4.6 V, and discharge rate of 0.1 C to 5.0 C using an electrochemical analyzer (Toyo, Toscat-3100) to measure the initial charge capacity, initial discharge capacity, initial reversible efficiency, and discharge capacity ratio.

[0163] The measurement results are shown in Tables 3 and 4 below.

[0164] [Table 3]

[0165] [Table 4]

[0166] Referring to the results of Tables 3 and 4, it can be seen that there are regions in the lithium manganese-based oxide where the ratio of the phase belonging to the C2 / m space group to the phase belonging to the R3-m space group is different, and when the mole number of nickel based on all metal elements (excluding lithium) in the phase belonging to the R3-m space group relative to all metal elements (excluding lithium) in the region where the phase belonging to the R3-m space group is predominantly present is within a predetermined range, the decrease in stability caused by excess amounts of lithium and manganese in the lithium manganese-based oxide is mitigated and / or prevented, thereby improving the discharge capacity and rate characteristics.

[0167] Although the embodiments of the present invention have been described above, a person having ordinary knowledge in the art may modify and change the present invention in various ways by adding, changing, deleting or adding elements without departing from the concept of the present invention described in the claims, and this may also be considered to be within the scope of the claims of the present invention.

Claims

1. A positive electrode active material comprising a lithium-excess lithium-manganese-based oxide containing at least lithium, nickel, and manganese, The lithium manganese-based oxide is a solid solution of a phase belonging to a C2 / m space group and a phase belonging to an R3-m space group, There are regions in the solid solution in which the ratio of a phase belonging to the C2 / m space group to a phase belonging to the R3-m space group is different; A positive electrode active material, wherein a concentration of a metal element in the lithium manganese-based oxide satisfies the following formula 2: [Formula 2] 0.40≦M2' / M1'≦0.70 where M 1′ is the number of moles of all metal elements (excluding lithium) in the phase belonging to the R3-m space group; M 2' is the number of moles of nickel based on all metal elements (excluding lithium) in the phase belonging to the R3-m space group.

2. The positive electrode active material according to claim 1 , wherein the concentration of the metal element in the lithium manganese-based oxide satisfies the following formula 1: [Formula 1] 0.24≦M 2 / M 1 ≦0.55 Where: M 1 is the number of moles of all metal elements (excluding lithium) in the lithium manganese oxide, M 2 is the number of moles of nickel based on all metal elements (excluding lithium) in the lithium manganese oxide.

3. The lithium manganese-based oxide is a core-shell particle including a core and a shell covering at least a part of the surface of the core, A phase belonging to the C2 / m space group and a phase belonging to the R3-m space group coexist in the core; 2. The positive electrode active material according to claim 1, wherein a ratio of the phase belonging to the R3-m space group to the phase belonging to the C2 / m space group in the shell is greater than a ratio of the phase belonging to the R3-m space group to the phase belonging to the C2 / m space group in the core.

4. The positive electrode active material according to claim 3 , wherein the concentration of the metal element in the shell satisfies the following formula 3: [Formula 3] 0.24≦M 4 / M 3 ≦0.75 Where: M 3 is the number of moles of all metal elements (excluding lithium) in the shell, M 4 is the number of moles of nickel based on all metal elements (excluding lithium) in the shell.

5. The positive electrode active material according to claim 3 , wherein the concentration of the metal element in the shell satisfies the following formula 4: [Formula 4] 0.40≦M 4′ / M 3′ ≦0.75 Here, M 3′ is the number of moles of all metallic elements (excluding lithium) in the phase belonging to the R3-m space group in said shell, M 4′ is the number of moles of nickel based on all metal elements (excluding lithium) in the phase belonging to the R3-m space group in said shell.

6. 4. The positive electrode active material according to claim 3, wherein the ratio of the phase belonging to the R3-m space group to the phase belonging to the C2 / m space group in the lithium manganese-based oxide has an increasing gradient from the core to the shell.

7. The positive electrode active material according to claim 3, wherein only a phase belonging to the R3-m space group is present in the shell.

8. The positive electrode active material of claim 1 , wherein the lithium manganese-based oxide is represented by the following Chemical Formula 1: [Chemical formula 1] rLi 2 MnO 3 ・(1-r)- a Ni x Co y Mn z M1 1-(x+y+z) O 2 Where: M1 is at least one selected from Mo, Nb, Fe, Cr, V, Cu, Zn, Sn, Mg, Ru, Al, Ti, Zr, B, Na, K, Y, P, Ba, Sr, La, Ga, Gd, Sm, W, Ca, Ce, Ta, Sc, In, S, Ge, Si and Bi; 0<r≦0.8, 0<a≦1, 0<x≦1, 0≦y<1, 0<z<1 and 0<x+y+z≦1.

9. A positive electrode comprising the positive electrode active material according to claim 1 .

10. A lithium secondary battery using the positive electrode according to claim 9.

Citation Information

Patent Citations

  • Lithium secondary battery positive electrode active material

    JP2011134670A

  • Positive electrode active material for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery arranged by use thereof

    JP2016033848A

  • Positive electrode active material, mixture electrode having the same, positive electrode for nonaqueous electrolyte secondary battery, and nonaqueous electrolyte secondary battery

    JP2016072179A

  • Cathode active material, method for preparing the same, and lithium secondary batteries comprising the same

    KR1020150069334A